Room‐Temperature Quantum Memories Based on Molecular Electron Spin Ensembles - Lenz, Samuel; König, Dennis; Hunger, David; Slageren, Joris (Advanced materials (Weinheim), 2021)
Whilst quantum computing has recently taken great leaps ahead, the development of quantum memories has decidedly lagged behind. Quantum memories are essential devices in the quantum technology palette and are needed for intermediate storage of quantum bit states and as quantum repeaters in long‐distance quantum communication. Current quantum memories operate at cryogenic, mostly sub‐Kelvin temperatures and require extensive and costly peripheral hardware. It is demonstrated that ensembles of weakly coupled molecular spins show long coherence times and can be used to store microwave pulses of arbitrary phase. These studies exploit strong coupling of the spin ensemble to special 3D microwave resonators. Most importantly, these systems operate at room temperature. Ensembles of weakly exchange coupled organic radicals form strongly coupled systems with 3D microwave resonators. Time‐domain pulsed microwave investigations reveal long, largely temperature‐independent quantum coherence times. The room‐temperature storage and retrieval of microwave pulses is demonstrated.